Validation of the Italian version of the Critical Pain Observation Tool in brain-injured critically ill adults - Sulla, Francesco; De Souza Ramos, Nilson; Terzi, Noemi; Trenta, Tania; Uneddu, Mariella; Zaldivar Cruces, Melanny Alessandra; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: Pain in intensive care units (ICUs) is a frequent and often undermanaged problem. Brain-injured patients are often unable to reliably self-report their pain, calling forth the need to use behavioural scales such as the Critical-Care Pain Observation Tool (CPOT). This study aimed to test the reliability and validity of the Italian CPOT use with brain-injured ICU adults. Method: A sample of 50 adults critical care patients was included. Each patient was assessed by two independent observers at three predefined times – at rest; during mobilization for hygiene; 20 minutes later – using the CPOT, PAINAD, and NRS. Results: A good correlation was found between independent observers scores during painful procedure, establishing interrater reliability of CPOT. Criterion validation was supported by a strong correlation between CPOT and PAINAD scores, and a moderate relation between CPOT and NRS scores. The CPOT was able to discriminate between patients undergoing painful versus non-painful procedures. However, PAINAD performed better in this sample, as revealed by the comparison between the two AUC of ROC curves. Conclusions: The Italian CPOT use was found reliable and valid in this patient group.